A Meta-analysis of the efficacy of non-pharmacological interventions in treating constipation symptoms in lung cancer patients (非药物干预措施治疗肺癌患者便秘症状疗效的Meta分析) - CAI Mian (蔡绵); YIN Jie (尹婕); XU Yiyong (徐义勇) (中西医结合护理)
Objective To comprehensively evaluate the efficacy of non-pharmacological interventions in treating constipation symptoms in lung cancer patients through meta-analysis, and provide evidence-based support for individualized clinical selection. Methods Researches published up by Jan 2025 were searched in PubMed, Embase, The Cochrane Library, Web of Science, CINAL, CNKI, Wanfang Database, VIP Database, and China Biomedical Network. Randomized controlled trials (RCTs) comparing non-pharmacological interventions with conventional or placebo treatment in adult lung cancer patients with constipation symptoms were included. Three authors independently conducted research screening. To use Cochrane RoB2 tool for quality assessment, and perform meta-analysis using Stata17. 0 software. Results A total of 15 studies (1470 participants) were included in this study. Non-pharmacological interventions showed better efficacy in treating constipation (OR=3. 41, 95%CI［1. 75, 6. 65］, P＜0. 01)and reducing first bowel movement time (SMD=-1. 5; 95%CI［-1. 75, -1, 24］, P＜0. 01) compared to the control group, with statistically significant differences. Conclusion Non-pharmacological interventions are effective and safe in treating constipation symptoms in lung cancer patients. (目的 通过Meta分析, 综合评价非药物干预措施治疗肺癌患者便秘症状的疗效, 为临床个体化选择提供循证依据。方法 检索PubMed、Embase、The Cochrane Library、Web of Science、CINAL、中国知网(CNKI)、万方数据库(Wanfang Data)、维普数据库(VIP)和中国生物医学网(CBM) , 检索时限为建库至2025年1月。纳入比较非药物干预措施与常规治疗或安慰剂治疗的随机对照试验(RCTs), 研究对象为成年肺癌患者且有便秘症状。由三位作者独立进行研究筛选。使用Cochrane RoB2工具进行质量评估。使Stata17. 0软件进行Meta分析。结果 本研究共纳入了15项(1470名参与者)研究。非药物干预能有效提高便秘症状治疗有效率(OR=3. 41, 95%CI［1. 75, 6. 65］, P＜0. 01); 非药物干预能有效缩短患者的首次排便时间(SMD=-1. 5; 95%CI［-1. 75, -1, 24］, P＜0. 01)。结论 非药物干预措施治疗肺癌患者便秘症状疗效确切, 安全性好。)